Complexities of Voice in the Poetry of William Wordsworth - Domines Veliki, Martina (2008)
The question of language in Wordsworthian criticism focuses today on the description of the difference within and between written and spoken discourses. Though Wordsworth was fascinated with all kinds of written language, he is also a poet of speech, “ a man speaking to men” (1800 Preface to Lyrical Ballads) with “ another ear” for the sounds and voices around him. The multifarious occurrences of sound/voice, as metonymic images of speech, do not serve only as a backdrop to Wordsworth’ s expression of the self but are a dynamic force shaping and affecting the “ I” of the poet. This paper looks at some of the greatest Wordsworth’ s poems such as The Prelude, the Intimations Ode, Tintern Abbey, Resolution and Independence, to see how the self grows from the child’ s silent reading of “ the eternal deep” , where his “ mute dialogues” do not refer to the absence of voice but rather to “ a communication, (… ) a speech deprived of speech, language deprived of speaking” (Warminski1987: 23) into the self of a poet-prophet hearing the voices to which others were oblivious – the voices of the poor and the oppressed in the heat of the French Revolution.
Projekt MZOS
ENG